A linguagem regional/popular do poeta Zé Vicente da Paraíba: glossário léxico-semântico - Santos, Wellington Lopes dos (2018)
The popular culture, in particular, poetry, repentes and cordel literature, are presented as important tools for linguistic analysis. These poetic works show in their stanzas a vocabulary characteristic characteristic of the sociocultural universe in which the author is inserted. They are, therefore, artistic productions that reveal an inexhaustible linguistic richness. In this perspective, the present work entitled: the regional / popular language of the poet Zé Vicente da Paraíba: lexico-semantic glossary has as main objective to elaborate a glossary of lexicosemantic nature of the regional / popular language identified in the works (poetry and songs) of author of Zé Vicente da Paraíba. These works accurately represent the richness of the regional / popular language of the Northeast region of Brazil. In this context, hundreds of these are registered and alive until the present day, enriching the northeastern culture and contributing to studies of an academic nature. Already countless others, especially improvised poetry, were lost in time for lack of written and audiovisual records. The corpus included 39 works (poetry and songs) that portray: 1) the social and cultural contexts of the Northeastern man who occupies diverse functions, among them: popular artist, farmer, cowboy and 2) the backlands with its riches and natural landscapes. The theoretical basis was based on the presuppositions of Dialecology: study of linguistic systems in their geographical or social variations (BORBA, 1976), Sociolinguistics: language and society (COSERIU, 1987), Ethnolinguistics: language and culture (COSERIU, 1987), Lexicology: study the lexical scientist (OLIVEIRA; ISQUERDO, 2001); (ARAGÃO, 2005), Lexicography: elaboration of dictionaries, vocabularies and glossaries (BIDERMAN, 2001) and Semantics: science of meaning (MARQUES, 1996); (TAMBA-MECZ, 2006).